Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen

CO2 electrolysis towards large scale operation: rational catalyst and electrolyte design for efficient flow-cell - Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (Chemical Communications, 2023)
The electrochemical CO2 reduction reaction (CO2RR) to renewable fuels/chemicals is a potential approach towards addressing the carbon neutral economy. To date, a comprehensive analysis of key performance indicators, such as an intrinsic property of catalyst, reaction environment and technological advancement in the flow cell, is limited. In this study, we discuss how the design of catalyst material, electrolyte and engineering gas diffusion electrode (GDE) could affect the CO2RR in a gas-fed flow cell. Significant emphasis is given to scale-up requirements, such as promising catalysts with a partial current density of >= 100 mA cm(-2) and high faradaic efficiency. Additional experimental hurdles and their potential solutions, as well as the best available protocols for data acquisition for catalyst activity evaluation, are listed. We believe this manuscript provides some insights into the making of catalysts and electrolytes in a rational manner along with the engineering of GDEs towards CO2RR.